A pharmacovigilance study on FDA approved interleukin inhibitor-associated alopecia in the treatment of psoriasis - Islam, Nahidul (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.